CORRELATION BETWEEN FAT CONSUMPTION, SMOKING HABIT, AND STRESS WITH HYPERTENSION AMONG DRIVERS - Mentari Indah Saputri; Lailatul Muniroh; Sobhita Paramita (Media Gizi Indonesia, 2020)
Hypertension is one of major health problem that aff ect many people. Driver is one of the jobs that could cause hypertension due to the surrounding environment which support unhealthy lifestyles such as consuming excessive fat, smoking habit and susceptible to stress. The purpose of this research was to analyze the correlation between fat consumption, smoking habit, and stress with hypertension among drivers. This research was an observational study using cross sectional design. The samples were 74 male drivers taken by accidental sampling. The respondent was chosen around Juanda Airport Sidoarjo. The data were collected by measuring blood pressure using digital sphygmomanometer and interview using questionnaire, Semi Quantitative Food Frequency Questionnaire, and The Workplace Stress Scale. The data then analyzed using Pearson and Spearman Correlation test. The results of this research showed that stress (P=0,000; r=0,830) had strongest correlation with hypertension among drivers compared to two other variables, fat consumption (P=0,000 ; r=0,689) and smoking habits (P=0,004 ; r=0,331). This study concludes that excessive fat consumption, smoking habit 11-20 cigarettes/day, moderate and severe stress levels can increase the risk of hypertension among drivers. Drivers should adjust to reduce consumption of fried foods, smoking habit, and stress with suffi cient rest ± 7-8 hours/day to prevent the occurrence of hypertension among drivers.